Human Resources Development: Women Role Optimization in the Local Government Bureaucracy in Central Sulawesi, Indonesia - Nuraisyah, Nuraisyah; Samad, Muhammad Ahsan (Journal of Asian Multicultural Research for Economy and Management Study, 2021)
Research on gender roles in relation to government bureaucratic structures is still minimal. This study aims to find answers to the main problem, namely how the role of women in the local government bureaucracy seen from human resource development aspect in Central Sulawesi Province. This research is a qualitative descriptive study which aims to create a picture of the gender presentation in the bureaucratic staffing and the role of women. The subjects of this study were women who hold echelons. The data collection technique used in this study was literature review. For the validity of the data, the cross check technique was used. The data analysis technique used is the inductive analysis technique. The results showed that the role of women in the local government bureaucracy in Central Sulawesi was still not fully implemented. The echelon holder ratio is still dominated by men. However, it is possible that this ratio will change over time.